Electron beam relaxation in inhomogeneous plasmas - A. Voshchepynets; V. Krasnoselskikh (Annales Geophysicae, 2013)
In this work, we studied the effects of background plasma density fluctuations on the relaxation of electron beams. For the study, we assumed that the level of fluctuations was so high that the majority of Langmuir waves generated as a result of beam-plasma instability were trapped inside density depletions. The system can be considered as a good model for describing beam-plasma interactions in the solar wind. Here we show that due to the effect of wave trapping, beam relaxation slows significantly. As a result, the length of relaxation for the electron beam in such an inhomogeneous plasma is much longer than in a homogeneous plasma. Additionally, for sufficiently narrow beams, the process of relaxation is accompanied by transformation of significant part of the beam kinetic energy to energy of accelerated particles. They form the tail of the distribution and can carry up to 50% of the initial beam energy flux.